Biofiltración de metanol por Pichia methanolica - Santana Olguín, Adriana (Universidad Autónoma Metropolitana, 2004)
Biofiltration is a clean technology in which a microbial consortium is cultivated and immobilized on to a support to eliminate gaseous polluting compounds generating mainly water, CO2 and biomass. This work focused on the biofiltration of methanol, a polluting volatile organic compound, mainly emitted by paper mill, wood, painting, pharmaceutical and chemical industries. Unlike for conventional biofiltration, where mixed cultures are used, a pure culture of the methylotrophic yeast Pichia methanolica was employed in this work. P. methanolica can be modified genetically so, methanol can be the carbon source and the inductor to the heterologous protein production at the same time. It is therefore fundamental, to promote the biomass generation and to limit the presence of contaminant microorganisms to promote its permanence in the biofilter. In order to characterize the yeast, the growth parameters and methanol consumption in liquid culture were evaluated. The maximum growth rate (µmax) was estimated to be 0.079 h-1. The three methods of biomass quantification used were correlated (optical density, dry weight and cellular count) permiting estimate the biofilter biomass by means o cellular counts. From microcosms experiments, it were determinated: the specific methanol consumption rate (qS) of 0.066 gmethanol/gbiomass•h, the maintenance coefficient (m) of 0.024 gmethanol/gbiomasa•h, the endogenous metabolism coefficient of 0.0013 gCO2/ gbiomass•h and the cell yield coefficient (YX/S) of 0.34 gbiomass/gmethanol. These parameters allowed to estimate the elimination capacity (EC) expected for the methanol biofiltration. From a qS of 0.066 gmethanol/gbiomass•h and the maximum biomass reached in biofilter (32.2 mg/gsupport dry), an ECmax of 220 g/m 3 •h was expected, close to the experimental value of 190 g/m3 •h. Through oximetry experiments, the major oxygen consumption was registered with methanol concentrations between 100 - 400 mmol/L (3.2 – 12.8 g/L) and apparently, there was no inhibition up to concentrations of 1526 mmol/L (48.8 g/L). In a similar way, it was determined that values of pH between 2 - 5 do not affect the methanol consumption. This information allowed to operate, in the biofiltration experiments, with acid pH and methanol concentrations up to 400mmol/L (12.8 g/L) in the liquid + support phase to limit the presence of contaminant microorganisms (mainly bacteria). The biofiltration experiments were realized in columns of 0.2L using perlite and sugar cane bagasse as supports. The results indicate that there is no inhibition of the yeast metabolism at concentrations of methanol up to 8.7 g/m3 in the gas phase. The methanol removal and the production of biomass were higher with perlite than with sugar cane bagasse. With perlite, an ECmax of 190 g/m3 •h was reached during 48 hours and a biomass of 32.2 mgbiomass /gsupport dry was obtained. With the sugar cane bagasse were obtained an ECmax of 165 g/m3 •h for 48 hours and a biomass of 26 mg/gsupport dry. In both cases, it was possible to operate the biofilters for 22 days without apparent contamination. Due to the incomplete moisture saturation of the gas stream and to the metabolic heat generated, the columns were dried. The recovery of the removal efficiency was obtained by adding water and/or mineral medium. No mixing was nedded. Furthermore, the periodic addition of mineral medium, unlike the water addition, promoted the production of biomass. The biofiltration process was scale up in a column of 1.1L packed with perlite. An ECmax of 110 g/m3 •h was reached at the 9th day and a black coloration in the top of the column at the 12th day indicated a fungi contamination. Initially, the pH value in the support was 5.0 and diminished quickly until values of 2.7, probably due to the presence of acidic intermediary such as formic acid. The acidic pH limited the bacterial contamination, but not the fungal contamination observed occasionally, probably, due to the manipulation of the columns and because the gas stream was not sterile. So, it was important to control the conditions of starting and operation of the biofilter. Principally, assuring the moisture saturation of the gas stream to avoid drying in the column and therefore the water addition, which represents a contamination risk. The methanol elimination capacity, of the fungal contamination in colums of 0.2 L was evaluated for 34 days. An ECmax of 235 g/m3 •h was obtained during 10 days (in liteature have been reported values among 85 – 380 g/m3 •h). For that reason this microorganism represents an important alternative in conventional biofiltration for the elimination of methanol. The contaminating fungus was isolated and identified as Aspergillus sp.; La biofiltración es una tecnología en la cual se emplea un consorcio microbiano cultivado e inmovilizado en un soporte para oxidar biológicamente los compuestos contaminantes gaseosos generando agua y CO2 principalmente. Este trabajo se enfocó a la biofiltración del metanol. A diferencia de un proceso de biofiltración convencional en donde se utilizan cultivos mixtos, se empleó un cultivo puro de la levadura metilotrófica Pichia methanolica. Esta podría ser modificada genéticamente para que a la par de consumir metanol produzca alguna proteína heteróloga de interés. Es por lo tanto fundamental, promover la generación de biomasa y limitar la presencia de microorganismos contaminantes. Con el fin de caracterizar a la levadura, se evaluaron los parámetros de crecimiento y consumo de metanol en medio líquido. Se determinó que la tasa de crecimiento máxima (µmáx) es de 0.079 h-1 y se correlacionaron los tres métodos de cuantificación de biomasa empleados (densidad óptica, peso seco y conteo celular) para posteriormente, mediante conteos celulares, realizar estimaciones de la biomasa presente en el biofiltro. En sistemas cerrados (microcosmos), se determinó que la velocidad específica de consumo de metanol (qS) es de 0.066 gmetanol/gbiomasa•h, el coeficiente de mantenimiento (m) de 0.024 gmetanol/gbiomasa•h, el coeficiente de respiración endógena de 0.0013 gCO2/ gbiomasa•h y el coeficiente de conversión de metanol en biomasa (YX/S) de 0.34 gbiomasa /gmetanol. Los parámetros de consumo de metanol en medio líquido permitieron estimar el comportamiento de la levadura en el biofiltro. Así, partiendo de qS y de la biomasa máxima alcanzada en biofiltro (32.2 mg/gsoporte seco), se calculó una capacidad de eliminación (CE) máxima de 220 g/m3 •h y experimentalmente se obtuvo una CEmáx de 190 g/m3 •h. Mediante experimentos de oximetría, se determinó que las concentraciones de metanol a las cuales se registra el mayor consumo de oxígeno son entre 100 – 400 mmol/L (3.2- 12.8 g/L) y que aparentemente no hay inhibición a concentraciones hasta de 1526 mmol/L (48.8 g/L). De manera análoga, se determinó que valores de pH entre 2 – 5 no afectan el consumo del metanol. Esta información permitió operar, en los experimentos de biofiltración, a pH ácido y concentraciones de metanol de hasta 400mmol/L (12.8 g/L) (fase líquida + soporte) para así limitar la presencia de microorganismos contaminantes (principalmente bacterias). Los experimentos de biofiltración se realizaron en columnas con un volumen de 0.2L empleando la perlita y el bagazo de caña como soportes. Los resultados indican que no hay inhibición del metabolismo de la levadura a concentraciones de metanol de hasta 8.7 g/m3 lo que corresponde, en la fase líquida + soporte, a 314 mmol/L (10 g/L). Un factor determinante en el comportamiento del biofiltro es el tipo de soporte. Así, la perlita, más que el bagazo, favoreció el proceso de remoción del metanol y la producción de biomasa. Con la perlita se alcanzó una capacidad de eliminación máxima (CEmáx) de 190 g/m3 •h durante 48 horas y una densidad de biomasa de 32.2 mg/gsoporte seco. Con el bagazo de caña se obtuvo una CEmáx de 165 g/m3 •h por 48 horas y una biomasa de 26 mg/gsoporte seco. En ambos casos fue posible operar los biofiltros hasta por 22 días sin contaminación aparente. Debido a la incompleta saturación de humedad de la corriente de alimentación y al calor metabólico generado hubo secado en las columnas. Por ello, se evaluó la recuperación de la eficiencia de remoción adicionando con o sin mezclado agua y/o medio mineral. Se determinó que es suficiente con la adición sin mezclado de la fase líquida. Además, la adición periódica de medio mineral, a diferencia de la adición de agua, promovió que se generara el doble de biomasa (18.5 y 9.57 mgbiomasa/gsoporte seco respectivamente). Respecto al pH, inicialmente su valor en el soporte fue alrededor de 5.0 el cual disminuyó rápidamente hasta alcanzar un valor aproximado de 2.7 debido a la presencia de compuestos intermediarios ácidos poco volátiles: probablemente ácido fórmico. El pH ácido limitó la contaminación bacteriana pero no la fúngica la cual se observó ocasionalmente probablemente por la manipulación de las columnas y a que el aire alimentado al biofiltro no era estéril. Se escaló el proceso de biofiltración para lo cual se empleó una columna con un volumen útil de 1.1L empacada con perlita. Se alcanzó una CEmáx de 110 g/m3 •h al 9º día y al 12º una coloración negra en la parte superior de la columna indicó una contaminación fúngica. Se evaluó la capacidad de eliminación de metanol de un hongo aislado e identificado como Aspergillus sp. el cual presentó un crecimiento importante en columnas de 0.2L. Se obtuvo una CEmáx de 235 g/m3 •h durante 10 días por lo que este microorganismo representa una alternativa importante en biofiltración convencional para la eliminación del metanol. Finalmente, resultó importante controlar las condiciones de arranque y de operación del biofiltro. Principalmente, asegurando la saturación de humedad del flujo de alimentación para evitar secado en la columna y por consiguiente adicionar agua lo que representa un riesgo de contaminación.